Copper metabolism and cuproptosis: broad perspectives in the treatment of hepatocellular carcinoma - Liang, Jiale; Wang, Ruting; Wu, Hongxi; Huang, Zhenjin; Zhang, Ruohan; Jiang, Feng (Frontiers in Oncology, 2025)
Copper is an essential trace element that plays a pivotal role in multiple biological processes, including energy production and angiogenesis. It is also a vital cofactor necessary for the maintenance of biological functions and has been implicated in cancer development. The recently identified form of cell death, cuproptosis, has a unique induction mechanism—accumulated copper ions directly bind to lipoylated proteins in the mitochondrial tricarboxylic acid (TCA) cycle, triggering toxic protein aggregation and cell death. This process can be specifically induced by oxidative stress and mitochondrial dysfunction, providing a novel direction for the development of anti-tumor strategies that target copper metabolism. In hepatocellular carcinoma (HCC), there is a significant correlation between disturbances in copper metabolism and abnormalities in the cuproptosis pathway. HCC cells maintain pro-carcinogenic copper levels through the upregulation of copper transporter proteins such as copper transporter 1 (CTR1). Conversely, the dysregulation of the expression of key genes involved in cuproptosis (ferredoxin 1, lipoic acid synthetase) may mediate treatment resistance. In this review, we focus on the mechanism by which cuproptosis influences the occurrence and development of HCC, evaluate its potential as a diagnostic biomarker, and examine therapeutic strategies targeting this form of cell death (nanocarrier-based delivery of copper ion carriers, CRISPR-mediated editing of copper-regulated genes). These strategies may provide a novel perspective for overcoming the current therapeutic limitations of HCC.